Nanoalloys : from fundamentals to emergent applications - Calvo, Florent (Elsevier Science, 2013)
The swiftly-evolving field of nanoalloys presents significant opportunity for industrially relevant research - particularly in energy, biosensors, data storage, optical devices and catalysis. This work, from a cluster of interdisciplinary nanoscientists led by CNRS's Florent Calvo, supports your end users' rapid production of impactful research at the cutting-edge intersection between fundamental physics and chemistry (synthesis, properties, characterization) and promising nanoengineered applications of the future.
Keywords: Nanostructured materials.; Alloys.; Microalloying.; Nanoparticles.; elektronické knihy; electronic books